Seekers of the face: secrets of the Idra rabba (the Great Assembly) of the Zohar - Helner-Eshed, Melilah (Stanford studies in Jewish mysticism, 2021)
Introduction to the Idra rabba -- The language of divine faces -- The gaze -- Reflections on Ze'eir Anpin -- Literature, mysticism, praxis -- Overarching themes in the Idra rabba -- What is the Idra rabba trying to communicate? -- Entering the Idra rabba -- The Kings of Edom : The first appearance -- Arikh Anpin : origins -- Arikh Anpin : features of the face -- Arraying Arikh Anpin's beard -- The Kings of Edom : the second appearance -- Ze'eir Anpin comes into being -- Ze'eir Anpin's head and its features -- The tiqqunim of Ze'eir Anpin : the language of flowing bounty -- The Ancient of Ancients and Ze'eir Anpin : all is one -- Forming the male and female body -- The Kings of Edom : the third appearance -- Separation and coupling -- Sweetening judgment -- Emerging from the Idra rabba